ONLINE LEARNING BASED ON HIGHER ORDER THINKING SKILLS IN ELEMENTARY SCHOOL: A CASE STUDY - Peduk Rintayati; Riyadi Riyadi; Ahmad Syawaludin (JURNAL TARBIYAH, 2024)
21st century learning is ideally designed with learning categorized as higher order thinking skills (HOTS). This study specifically aims to describe the implementation of online learning in the HOTS category in elementary schools. This research will be conducted on fifth grade students in elementary school in Surakarta. This research uses a qualitative approach with a case study method. Analysis of learning implementation is carried out at the stages of learning planning, learning implementation, and learning assessment. The results showed that at the planning stage, the teacher analyzed the syllabus and content as well as selecting materials, developing teaching materials. At the implementation stage, the teacher uses a whatsapp group and google meet. The technique used is a mixture of synchronous and asynchronous. Students document learning activities such as presentations or simple experiments and upload them via the google classroom link with the design referring to levels C4, C5, and C6. The teacher's analysis and responses are given after the students have collected their exam answers. The results of this study are expected to be a reference source for teachers to make adjustments to the implementation of online learning that allows for stimulating HOTS of students in elementary schools.21st century learning is ideally designed with learning categorized as higher order thinking skills (HOTS). This study specifically aims to describe the implementation of online learning in the HOTS category in elementary schools. This research will be conducted on fifth grade students in elementary school in Surakarta. This research uses a qualitative approach with a case study method. Analysis of learning implementation is carried out at the stages of learning planning, learning implementation, and learning assessment. The results showed that at the planning stage, the teacher analyzed the syllabus and content as well as selecting materials, developing teaching materials. At the implementation stage, the teacher uses a whatsapp group and google meet. The technique used is a mixture of synchronous and asynchronous. Students document learning activities such as presentations or simple experiments and upload them via the google classroom link with the design referring to levels C4, C5, and C6. The teacher's analysis and responses are given after the students have collected their exam answers. The results of this study are expected to be a reference source for teachers to make adjustments to the implementation of online learning that allows for stimulating HOTS of students in elementary schools.